Improvement of Li-S battery electrochemical performance with 2D TiS2 additive. (1st December 2018) - Sun, Ke; Fu, Maosen; Xie, Zhenhua; Su, Dong; Zhong, Hui; Bai, Jianming; Dooryhee, Eric; Gan, Hong
Abstract: As a multifunctional cathode additive, TiS2 has been used in Li-S batteries to promote sulfur utilization and improve cell cycle life. The improvement of Li-S cell electrochemical performance in the presence of TiS2 has been attributed to the ability of TiS2 in adsorbing polysulfide. To maximize the interaction between polysulfides and TiS2, the 2-dimensional (2D) TiS2 nano-sheets with highly exposed TiS2 surface area has been successfully synthesized by a two-step sonication synthetic procedure. The 2D TiS2 particles are micron size in the basal plane direction and are nano-sized along the c-axis direction. 2D TiS2 nano-sheets may adsorb polysulfides more effectively than the raw TiS2 powder. Li-S cells with 2D TiS2 nano-sheets additive exhibit better discharge rate capability and significantly reduced capacity-fading after a long term cell cycling. This improvement can be partially attributed to the uniform distribution of 2D TiS2 nano-sheets particles within the sulfur cathode matrix, which induces more uniform sulfur and lithium sulfide deposition during the cell charge and discharge.